Grammatical Devices In The Theses Written By Graduate Students - Jemadi, Fransiskus (Jurnal Pendidikan dan Kebudayaan Missio, 2017)
The objective of this present study was to analyze the type of cohesive devices used in the theses of graduate students of English as a foreignlanguage. The data obtained for this discourse analysis study was gathered from the theses of 21 graduate students’ background of the study section at English Study Program Widya Mandala Catholic University Surabaya upon considering some set criteria. The results of this study indicated that the graduate students employed grammatical cohesive devices where reference was the most frequently used (80.14%), followed by conjunction (19.22%), ellipsis(0.47%) and substitution (0.15%). As far as the finding of this present study is concerned, the background of the study section of the graduate students’ theses seemed to be very cohesive through the use of reference and conjunction.The use of these two cohesive devices would serve not only to link the sentences together but also enable the readers to understand the text. Therefore, in the light of this finding, some pedagogical implications should be taken intoconsideration especially to teach explicitly about cohesive devices to students so that they would be able to compose a cohesive writing.